Analgesic and anti-inflammatory articular effects of essential oil and camphor isolated from Ocimum kilimandscharicum Gürke leaves - dos Santos, Elisangela; Leitão, Maicon Matos; Aguero Ito, Caren Naomi; Silva-Filho, Saulo Euclides; Arena, Arielle Cristina [UNESP]; Silva-Comar, Francielli Maria de Souza; Nakamura Cuman, Roberto Kenji; Oliveira, Rodrigo Juliano; Nazari Formagio, Anelise Samara; Leite Kassuya, Cândida Aparecida (Elsevier, 2021)
Ethnopharmacological relevance: Leaves from Ocimum kilimandscharicum Gürke (Lamiaceae) are popularly used against articular pain. Aim of study: The aim of this study was to test the anti-inflammatory and anti-hyperalgesic (analgesic) properties of the essential oil and camphor isolated from O. Kilimandscharicum leaves (EOOK) in 4 models including zymosan induced-articular inflammation model in mice. Material and methods: For in vivo models, EOOK was tested in carrageenan-induced paw edema model with oral doses of 30, 100, and 300 mg/kg (oral administration = p.o.) and in zymosan-induced articular inflammation (including knee edema, leukocyte infiltration, mechanical hyperalgesia and nitric oxide), EOOK (100 mg/kg, p. o.) and camphor (30 mg/kg, p. o.) were tested. EOOK (100 mg/kg, p. o.) was tested in the rolling and also in the adhesion of leukocytes to the mesenteric microcirculation in situ model of carrageenan induced inflammation and EOOK (1, 3, 10, 30, and 60 μg/mL) was tested in vitro against neutrophils chemotaxis induced by N-formyl methionyl leucyl phenylalanine (fMLP). Results: The treatment with EOOK significantly inhibited the carrageenan-induced edema, mechanical and cold hyperalgesia. Both, EOOK and camphor inhibited all articular parameters induced by zymosan. In situ intravitral microscopy analysis, EOOK significantly inhibited carrageenan-induced leukocyte rolling and adhesion. In vitro neutrophils chemotaxis, EOOK inhibited the leukocyte chemotaxis induced by fMLP. Conclusions: The present study showed that EOOK inhibited pain and inflammatory parameters contributing, at least in part, to explain the popular use of this plant as analgesic natural agent. This study also demonstrates that camphor and some known anti-inflammatory compounds present in EOOK could contribute for analgesic and anti-inflammatory articular properties.
Keywords: Anti-hyperalgesic; Articular; Camphor; Inflammation; Joint; Ocimum kilimandscharicum